2014
DOI: 10.1111/jopr.12189
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Guiding Flange Appliance in Correcting Mandibular Deviation in the Hemi‐Mandibulectomy Patient. A Correlative Study

Abstract: Percentage correction of mandibular deviation is dependent on the timing of prosthetic rehabilitation. The less the initial deviation, the better the correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Tripathi et al found that percentage of deviation correction is inversely proportional to duration elapsed between surgical phase and prosthesis insertion and amount of initial deviation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Tripathi et al found that percentage of deviation correction is inversely proportional to duration elapsed between surgical phase and prosthesis insertion and amount of initial deviation [10].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical excision of unilateral mandible causes the mandible to deviate toward the extirpated side with the loss of occlusal contact . Dentulous patients can be retrained to achieve acceptable maxillomandibular relationship with the help of appliance like guide plane . The success of mandibular guide flange appliance depends on early placement of the appliance preferably as soon as the immediate postsurgical sequelae have subsided .…”
Section: Discussionmentioning
confidence: 99%
“…Most dental literature shows prosthetic management of partially edentulous Cantor Curtis Class II, III and IV hemi-mandibulectomy patients, where tooth-supported prosthetic appliances can help limit deviation. 3,4 While, dental literature lacks clear documentation on the prosthetic rehabilitation of completely edentulous Cantor Curtis Class II, III and IV hemi-mandibulectomy cases, mostly showing some surgical intervention. 5…”
Section: Introductionmentioning
confidence: 99%